Recurrent Generalized Seizures with Postictal Todd’s Paralysis Caused by Medication-Associated Severe Hypomagnesemia: A Case Report - Abdalla Khalil (Karger Publishers, 2021)
Hypomagnesemia is one of the electrolyte disturbances that can cause seizures. It is common in the hospitalized patients and can be induced by long-term usage of many medications. A 68-year-old male known to have hypertension and gastroesophageal reflux presented to the Emergency Department with an unprovoked first seizure at home followed by a temporary right-sided hemiparesis, dysphasia, and facial asymmetry. The hemiparesis, dysphasia, and facial asymmetry resolved within less than an hour after the seizure. His serum potassium was low with prolonged QT interval in the electrocardiogram (serum magnesium was not checked in the Emergency Department). He received intravenous IV potassium chloride infusion, and his serum potassium level was corrected, but he had a recurrent seizure after 10 h. At that time, his serum magnesium was found to be very low, he received IV magnesium sulfate infusion, and his indapamide, omeprazole, and metformin medications were stopped. He had no further seizures, the rest of his blood tests were normal, and his CT brain was unremarkable. He was treated for aspiration pneumonia, and his outpatient MRI brain and EEG came to be normal too.